About the “Freedom of Choice” and the “Linguistic Balance” in Education: an Empirical Analysis of the Galician Parliamentary Discourse About the Language Distribution Decrees - Gradín, Mario (Madrygal. Revista de Estudios Gallegos, 2021)
The main objective of this research is to analyze the empirical base of the arguments that were used in five parliamentary debates about Decrees 124/2007 and 79/2010, the last two that determine the distribution of the two official tongues in Galician lower-level education (preschool to high school levels). To comprehend the reasons of the ideological and political differences that separate both decrees, we analyze five parliamentary debates where these topics are discussed, contrasting the arguments that are used in the interventions by the deputies with other sources, so that we can understand the context of the debate about languages that was present in Galicia between 2007 and 2010.